A cross-sectional single-centre study of anaemia in the elderly - Uriah, Simon; Oguzor, Ununuma; Uzosike, Tondor Cleopatra; Omunakwe, Hannah E. (International Journal of Research in Medical Sciences, 2023)
Background: The geriatric population is increasing globally, and anaemia in the elderly is associated with increased morbidity and mortality. The Anaemia in Elderly study (ANiE study) aimed to assess the prevalence, associations and severity of anaemia in elderly patients attending the outpatient clinics at Rivers State University Teaching Hospital. Methods: This was a prospective cross-sectional study of consenting patients, 60 years and older, attending the outpatient clinics in our hospital. A blood sample was collected for full blood count, blood glucose, serum creatinine and HIV serology. A data collection tool was used to collect data on comorbidities, occupation and income among others. Descriptive analysis and logistic regression were done to determine factors associated with anaemia in elderly patients in the outpatient clinics. Results: A total of 288 patients consented to participate, anaemia was prevalent in 101 (35.1%) of the participants, there was no difference in the prevalence between males and females, the mean PCV was 38.33±1.33%, the majority of the anaemic patients had mild anaemia 46 (45.5%). Being a patient on follow-up visit to the hospital, the average monthly income and employment status were significantly associated with the occurrence of anaemia. Conclusions: Anaemia according to the WHO definition was prevalent in 35.1% of elderly patients attending the out-patients’ clinics in the hospital. Factors associated with anaemia were employment status and average monthly income. It is important to identify patients at risk and provide appropriate care to prevent further morbidity and mortality.